RANCANG BANGUN SISTEM PENGHITUNGAN HEART RATE MENGGUNAKAN SENSOR FINGER - Ria Eksaktania, Tri Rijanto, Elly Indahwati (Reaktom : Rekayasa Keteknikan dan Optimasi, 2019)
Making heart rate module aims to obtain information module accuracy compared to standard gauge (Pulse Oxymetri). Work system which used using finger and sensor-based Arduino Uno which results are displayed on the LCD. This research uses the method by means of comparing the results of calculating heart rate on the module with the standard gauge (pulse oxymetri) conducted in 5 respondents, each of the respondents was conducted 5 times of measurement. The measurement is done by way of a coexisting between module and checklists (pulse oxymetri) on the index finger of the right and left using the finger sensor. The results of this study showed this tool be eligible to use the benchmarking measurement using Pulse with Oxymetri as much as 5 times by 5 respondents with an average error of results of 0.38%.